Rapid determination of the migration parameters of nuclides in intact granite rock under the action of electric field - Xinyu Wang; Xiaojie Li; Yongmei Li; Longcheng Liu; Shuo Meng; Chunguang Li; Zhenzhong Liu; Xiaodong Li; Kaixuan Tan (Nuclear Engineering and Technology)
Deep geologic disposal has been widely accepted as a strategy for long-term disposal of the high-level radioactive waste. It is principal to obtain the migration parameters of radionuclides in natural barrier, such as granite, of a high-level radioactive waste repository for safety assessment of the repository. To quickly determine the diffusion and sorption properties of nuclides in intact granite, two tracers, I− and ReO4−, were tested with a modified electromigration device, by imposing a constant voltage over an intact Beishan granitic rock sample. The breakthrough curves of I− and ReO4− were obtained under condition of five different voltages. To interpret the electromigration experimental results with more confidence, an advection-dispersion model based on first-order adsorption kinetics was developed in this study. Data analysis of the breakthrough curves by this model suggest that the effective diffusion coefficients of I− and ReO4− in intact Beishan granodiorite rock are (6.81 ± 0.53) × 10−13 m2/s and (6.45 ± 0.07) × 10−13 m2/s, respectively. While the distribution coefficient of the two ions are (9.06 ± 1.13) × 10−7 m3/kg and (9.81 ± 0.13) × 10−7 m3/kg, respectively. This indicates that I− and ReO4− hardly adsorb in Beishan granodiorite rock.